2004
DOI: 10.1007/s11745-004-1283-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of low density lipoprotein oxidation by FTIR and chemometric analysis

Abstract: This study was conducted to develop a quantitative FTIR spectroscopy method to measure LDL lipid oxidation products and determine the effect of oxidation on LDL lipid and protein. In vitro LDL oxidation at 37 degrees C for 1 h produced a range of conjugated diene (CD) (0.14-0.26 mM/mg protein) and carbonyl contents (0.9-3.8 microg/g protein) that were used to produce calibration sets. Spectra were collected from the calibration set and partial least squares regression was used to develop calibration models fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
(23 reference statements)
0
15
0
1
Order By: Relevance
“…S2(a) Supplementary Fig. S2b) was due to N-H stretching of peptide linkages of the polypeptide chain of lipoproteins (Lam et al, 2004). Furthermore, the high intensities of peaks observed in strain JA194 T ( Supplementary Fig.…”
Section: Strains Ja194mentioning
confidence: 97%
“…S2(a) Supplementary Fig. S2b) was due to N-H stretching of peptide linkages of the polypeptide chain of lipoproteins (Lam et al, 2004). Furthermore, the high intensities of peaks observed in strain JA194 T ( Supplementary Fig.…”
Section: Strains Ja194mentioning
confidence: 97%
“…Blood samples from five fasting human males were obtained in vacutainers containing 1 mg/mL EDTA and centrifuged for 10 min at 2000 × g and 4°C to separate the plasma. Human LDL were isolated from the fresh human plasma by sequential floating ultracentrifugation, according to the method described by Lam et al (9). The protein content of LDL was determined according to Lowry et al (10) with BSA as a standard.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to oxidation, all LDL samples were diluted to a final concentration of 50 µg of protein/mL with EDTA-free phosphate buffer (pH 7.4). The in vitro oxidation of LDL was performed in the absence (control) or presence of 0.5 µM quercetin, 2.0 µM catechin, and 0.05 µM α-tocopherol (in ethanol) per mg LDL protein, as previously described (9). The concentrations of quercetin, catechin, and α-tocopherol used in this study corresponded to those reported in human plasma (4,11,12) and will from here on also be referred to as their physiological concentrations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations